Referral Patterns in Oral Medicine: A Retrospective Analysis of an Oral Medicine University Center in Southern Italy - Noemi Coppola (MDPI AG, 2021)
Referral of a patient from one healthcare provider to another is an important part of the medical practice. The aim of this study was to analyze the referral process to the Oral Medicine Unit in a university-based tertiary center in Southern Italy. A chart review of new referrals to the Oral Medicine Unit during a 24-month period was conducted. The following data were recorded: demographic characteristics, medical history, number of physicians seen prior to Oral Medicine assessment, referral source, diagnostic procedures ordered by referrals, reason for referral, site of lesion/condition, final diagnosis. Then, the rates of correct identification for health-care professionals and the appropriateness of the reference diagnosis based on the disease were calculated with descriptive statistic indicators. There were 583 new first consultations. A total of 62.9% of patients were referred by general dental practitioners, 27.4% by physicians, and 9.7% did not have a referral. The most common diseases for referral were immune-mediated diseases (39.6%) and oro-facial pain disorders (25.2%). Only 28.5% of patients had a correct provisional diagnosis. The results of this study show the need to implement curricula in the field of oral medicine among dentistry and medical students, and to support the continuing education among healthcare providers to reduce diagnostic delay for oral diseases.